Plasma Organochlorines and Subsequent Risk of Prostate Cancer in Japanese Men: A Nested Case–Control Study - Sawada, Norie (National Institute of Environmental Health Sciences, 2010)
BACKGROUND: Although accumulating evidence suggests that exposure to organochlorine pesticides and polychlorinated biphenyls (PCBs) may contribute to the development of prostate cancer, few investigations have used biological samples to classify exposure to specific organochlorines. To our knowledge, this is the first prospective study to investigate the association between blood levels of organochlorines and prostate cancer risk. METHODS: We conducted a nested case–control study using data from the Japan Public Health Center–based Prospective (JPHC) Study. A total of 14,203 men 40–69 years old who returned the baseline questionnaire and who provided blood samples were followed from 1990 to 2005. Using a mean follow-up period of 12.8 years, we identified 201 participants who were newly diagnosed with prostate cancer. Two matched controls for each case were selected from the cohort. We used a conditional logistic regression model to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for prostate cancer in relation to plasma levels of nine organochlorines: PCBs, dichlorodiphenyltrichloroethane (DDT), hexachlorobenzene (HCB), β-hexachlorocyclohexane (β-HCH), trans- and cis-nonachlor, oxychlordane, and mirex. RESULTS: No statistically significant association with total prostate cancer was seen for any plasma organochlorine, although we did observe an insignificant inverse association for plasma HCB and β-HCH. Total PCB in plasma was also inversely associated with advanced prostate cancer but without statistical significance. CONCLUSION: Our results suggest that no overall association exists between prostate cancer and organochlorines at the levels measured in our study population.